1995
DOI: 10.1139/g95-158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within the species Arachis duranensis Krapov. &W.C. Gregory, a possible progenitor of cultivated peanut

Abstract: Eighteen accessions of a diploid wild peanut species (Arachis duranensis) were analyzed using morphological, intercrossing, cytological, and RFLP data. Abundant variation was found for morphological characters and for RFLP patterns both between and within accessions, and each accession could be uniquely identified by RFLP pattern. Several plants were found to be F1 hybrids between different accessions, indicating that intercrossing had occurred when these were planted for seed increase. Patterns of RFLP divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Previous research found a low frequency (0.01-0.26/PMC) of multivalents in 12 of 27 hybrids from crosses of A . duranensis accessions [69], and quadrivalents were identified in all these 12 hybrids, which likely represents chromosome translocations within this species. The asymmetrical chromosomes found in different accessions, furthermore, indicated the presence of translocations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found a low frequency (0.01-0.26/PMC) of multivalents in 12 of 27 hybrids from crosses of A . duranensis accessions [69], and quadrivalents were identified in all these 12 hybrids, which likely represents chromosome translocations within this species. The asymmetrical chromosomes found in different accessions, furthermore, indicated the presence of translocations.…”
Section: Resultsmentioning
confidence: 99%
“…RAPD data also suggested they are very closely related [37]. F 1 hybrids between accession GK 12787 of A. pintoi and accession GKP 10538 of A. repens , which represent the extreme types, had 86.8% pollen fertility [55], which is higher than the level of pollen fertility found in intraespecific hybrids of crosses between accessions of some other Arachis species [45,60]. …”
Section: Resultsmentioning
confidence: 99%
“…The data suggested that cross-pollination happens in some Arachis species. Evidences of cross-pollination in A. duranensis were found when different accessions were analyzed using RFLP [37]. The extensive polymorphism detected within accessions of A. cardenasii using cDNA and seed storage proteins probes [5,38,39] has also been suggested to be related to high frequency of cross-pollination.…”
Section: Resultsmentioning
confidence: 99%